A simplified point-of-care testing approach for preeclampsia blood biomarkers based on nanoscale field effect transistors. Issue 28 (12th July 2021) - Pham, Thuy Thi Thanh; Tran, Duy Phu; Nguyen, Minh Cong; Amen, Mohamed Taha; Winter, Marnie; Whitehead, Clare; Toh, Justine; Thierry, Benjamin
Abstract : We first present and pilot clinically validate a fully integrated, high-performance indium oxide nano-transistor biodiagnostic platform for rapid, accurate testing of preeclampsia without analytical equipment aids and minimum operator intervention. Abstract : Rapid diagnosis of preeclampsia is necessary to ensure timely administration of appropriate care and prevent the potentially catastrophic complications of the condition affecting both mothers and babies. While the diagnostic superiority of angiogenic blood biomarkers such as placental growth factor has recently been demonstrated, there is an urgent need to develop point-of-care (PoC) technologies that allow rapid, quantitative, and accurate testing for these markers within local communities. Towards addressing this need, here we report on a fully integrated biodiagnostic platform based on nanoscale indium oxide field effect transistor (FET) sensors. The high-performance FET sensors are integrated with blood sample processing cartridges that minimize the need for operator intervention during the assay and eliminate the need for analytical equipment. Within 40 minutes and from 30 μL of blood, the FET platform could reliably measure PlGF with a limit of detection of 0.06 pg mL −1 and a five order of magnitudes dynamic range. Pilot clinical validation in four preeclamptic pregnancies confirmed that the accuracy and reliability of the FET platform, paving the way for further development to a much-needed point-of-care preeclampsia testing.